(N{KOLXNYJ ATLAS(B-(NOPREDELITELX WYS[IH RASTENIJ (B:s (NkN(B. (NDLQ U^A]IHSQ (B/s - (NnOWIKOW(B, (NwLADIMIR sERGEEWI^(B,s; (NgUBANOW(B, (NiWAN aLEKSEEWI^s ((NmOSKWA (B:s (NpROSWE]ENIE(B,s, 1991)
(NaTLAS POMOVET OPREDELITX SEMEJSTWO I ROD NEIZWESTNOGO RASTENIQs
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NbOTAN)QÆKAs)E -- (NrOSLINIs; (NROSLINIs; (NWIDIs